The untapped promise of secondary data sets in international and comparative education policy research - Chudgar, Amita; Luschei, Thomas F (Education Policy Analysis Archives, 2016)
The objective of this commentary is to call attention to the feasibility and importance of large-scale, systematic, quantitative analysis in international and comparative education research. We contend that although many existing databases are under- or unutilized in quantitative international-comparative research, these resources present the opportunity for important, policy-relevant descriptive studies. We conclude the commentary with overarching observations about the strengths and limitations of such secondary data-based analysis.